An Unusual Stress Fracture in an Archer with Hypophosphatasia - Umut Yavuz; Sami Sökücü; Bilal Demir; Evren Akpınar; Osman Lapçin; Yunus Atıcı; Yavuz Kabukçuoğlu (Case Reports in Orthopedics)
We report a 45-year-old male archer with stress fracture in his left ulna on the background of adult type of hypophosphatasia. The patient presented to several medical centers for pain around the left elbow and received medical treatment upon diagnosis of tenosynovitis. History of the patient revealed that he had had diagnosis of hypophosphatasia ten years ago and underwent percutaneous screwing for stress fracture on both of his femoral necks. Upon finding nondisplaced stress fracture on proximal metaphysis of the ulna on X-ray, the patient underwent magnetic resonance imaging (MRI) in order to exclude pathological causes. No additional pathology was observed in MRI scanning. The patient’s sportive activities were restricted for 6 weeks and he received conservative management with arm slings. Adult type of hypophosphatasia is a disease manifesting with widespread osteoporosis and presenting with low serum level of alkali phosphatase (ALP). Stress fracture should definitely be considered in the patients with history of hypophosphatasia and refractory extremity pain.